Titans : beast world - Taylor, Tom, 1978- (DC Comics, 2024)
"Superman, Wonder Woman, Batman--all are powerless to stop the Necrostar from ending all life on Earth. The only hero who can save the world is...Beast Boy?! With Nightwing, Raven, Cyborg, and the Titans beside him, can Garfield Logan rise to battle an ancient evil? What will Amanda Waller do to take advantage of the situation as millions of people-including many of DC's iconic heroes!-are changed into rampaging creatures? Can humanity survive all-powerful heroes and villains transformed into ferocious beasts? And as the world goes wild, can Raven discover a way to save Beast Boy? If that's not enough... who is Dr. Hate, a mysterious new threat unleashing their own unique brand of chaos! Friends will fall. Heroes will rise. And nothing will ever be the same again. Earth is about to become... Beast World."--